Die Rolle des PSMA-PET/CT bei Patienten mit metastasiertem Prostatakarzinom = The role of PSMA PET-CT in patients with metastatic prostate cancer - Hardenberg, Jost von; Büsing, Karen-Anett; Nuhn, Philipp; Ritter, Manuel (Der Radiologe, 2018)
Prostate-specific membrane antigen (PSMA) positron emission tomography-computed tomography (PET-CT) imaging for the localization of prostate cancer is increasingly available in Germany. The advances and limitations in different disease stages are reviewed. As the clinical relevance of oligometastatic disease in primary cancer detected by PSMA PET-CT imaging is not yet completely understood, it should only be used in clinical trials. In recurrent prostate cancer after therapy with curative intent, PSMA PET-CT shows encouraging potential for the planning of salvage therapy. In metastatic castration-resistant prostate cancer evidence for its use is not available.
Gesehen am 05.04.2019